A quantitative analysis of the nerve fibres of the acetabular periosteum of dogs - Schmaedecke, A.; Saut, J. P. E.; Ferrigno, C. R. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
There are many techniques for the treatment of hip dysplasia, and novel research is currently being undertaken in the hope of obtaining more efficient and less traumatic techniques. The denervation of the hip joint capsule is a simple and effective technique that allows recovery of the functional activity of the affected limbs in significantly less time than other techniques. This surgical procedure consists of removing the acetabular periosteum, thus eliminating the nerve fibres with consequent analgesia. The aim of this investigation was to quantify the number of nerve fibres present in different regions of the acetabular periosteum. The knowledge of regional differences is potentially valuable for the refining of the denervation technique of the hip joint capsule. Thirty canine acetabular fragments were used to compare the nerve fibre density of the periosteum. The results showed a significant difference between the mean density of nerve fibres at the cranial and dorsallateral portion (approximately 75 fibres/mm2) and caudal lateral portion (approximately 60 fibres/mm2) of the acetabulum. Those fibres at the periosteum are almost positioned in a sagittal plane, pointing towards the joint capsule, suggesting the same density in the latter region. These results indicate a new approach to the articular denervation technique, thus obtaining even better results for the treatment of hip dysplasia in dogs.
Keywords: Acetabulum; nerve fibres; hip dysplasia; analgesia; dogs